Ekstrak Kulit Buah Manggis (Garcinia mangostana Linn) Mampu Meminimalkan Efek Imunosupresif Monosodium Glutamate (EFFECTIVENESS OF MANGOSTEEN PEEL EXTRACT (GARCINIA MANGOSTANA LINN) IN MINIMIZING THE IMMUNOSUPPRESSIVE EFFECT OF MONOSODIUM GLUTAMATE) - Bramardipa, Anak Agung Bagus; Adi, Anak Agung Ayu Mirah; Putra, I Gusti Agung Arta (Jurnal Veteriner; Vol 20 No 2 (2019), 2019)
Monosodium glutamate (MSG) is commonly used as a food additive or flavoring worldwide, unfortunately MSG is reported to have a toxic effect to the immune system, that can lead to an immunosuppressive conditions. One of immunosuppressive signs in chickens is atrophy of bursa Fabricius (BF). Mangosteen peel extract contains active substances and other components that can act as an immunomodulator. The aim of this study was to evaluate the immunosuppressive effects of MSG and the effectiveness of mangosteen peel extract in minimizing the immunosuppressive effects of the MSG. This study used a completely randomized design with four treatments namely A, B, C and K consisted four chickens each. The chickens in treatment A, B, C and K were given feed containing MSG 20% W/W and mineral water for drinking, commercial feed and mineral water containing 2% W/V mangosteen peel extract, MSG 20% W/W and mineral water containing mangosteen peel extract 2% W/V and commercial feed and drinking water without mixture. (control), respectively. Based on the results of this study, it was found that the administration of feed containing 20% MSG could result in bF atrophy with a very low bF index (p <0.01) if compared with B, C, and K-treatment. Prominet histopathological (HP) features of bF of chickens under treatment A are follicular atrophy and interfollicular edema. Treatment with feed containing 20% MSG along with the administration of drinking water containing 2% mangosteen peel extract keeps on maintaining the bF under normal condition even microscopically was found macrophages proliferation inside the lymphoid follicle. Based on clinical symptoms, index of bF and histopathological features, it can be concluded that MSG has immunosuppressive effects on chicks and mangosteen peel extract in drinking water can minimize this effect.